Mutation of hilD in a Salmonella Derby lineage linked to swine adaptation and reduced risk to human health - Martina Tambassi (Nature Portfolio, 2020)
Abstract Salmonella enterica variants exhibit diverse host adaptation, outcome of infection, and associated risk to food safety. Analysis of the distribution of Salmonella enterica serovar Derby (S. Derby) subtypes in human and swine identified isolates with a distinct PFGE profile that were significantly under-represented in human infections, consistent with further host adaptation to swine. Here we show that isolates with this PFGE profile form a distinct phylogenetic sub-clade within S. Derby and exhibit a profound reduction in invasion of human epithelial cells, and a relatively small reduction in swine epithelial cells. A single missense mutation in hilD, that encodes the master-regulator of the Salmonella Pathogenicity Island 1 (SPI-1), was present in the adapted lineage. The missense mutation resulted in a loss of function of HilD that accounted for reduced invasion in human epithelial cells. The relatively small impact of the mutation on interaction with swine cells was consistent with an alternative mechanism of invasion in this pathogen-host combination.